Computer aided dual padding design for burn injury - Salleh, Mohamed Najib; Acar, Memis; Burns, Neil D. (2014)
This paper reports a computational method to develop customized dual padding to be inserted at certain body parts with double low pressure areas. The results show that both custom made paddings can be created computationally.It is hope that the method can help occupational therapists to design padding that can exert the pressure close to the specific design pressure to the whole of the affected body part, which in turn offers an advantage for the healing process and the prevention of the formation of scar tissue due to burn injury.